2007
DOI: 10.1177/0003319707300368
|View full text |Cite
|
Sign up to set email alerts
|

QT Interval Analysis in Patients With Chronic Liver Disease: A Prospective Study

Abstract: In previous studies, it has been shown that QT interval prolongation is related to an increased mortality rate in chronic liver disease (CLD). But QT dispersion (QTd) and its clinical significance in CLD has not been well studied. The objectives of this study were to investigate the relation between QTd and severity of the disease and determine its prognostic value in cirrhotic patients. Thirty-three consecutive patients with cirrhosis and 35 sex- and age-matched healthy subjects were studied. QT intervals and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 26 publications
6
29
0
Order By: Relevance
“…Whereas these findings with regard to QTc are confirmatory of previous data (12,13), our findings of a longer QTmax, QTmin, QTdisp and TpTe could appear original, owing to the fact that, to our knowledge, no study has addressed the whole spectrum of electrocardiographic markers of ventricular repolarization in cirrhotic patients. It has been suggested that the prolongation of the QT interval in cirrhotic patients is associated with a greater severity of liver disease.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Whereas these findings with regard to QTc are confirmatory of previous data (12,13), our findings of a longer QTmax, QTmin, QTdisp and TpTe could appear original, owing to the fact that, to our knowledge, no study has addressed the whole spectrum of electrocardiographic markers of ventricular repolarization in cirrhotic patients. It has been suggested that the prolongation of the QT interval in cirrhotic patients is associated with a greater severity of liver disease.…”
Section: Discussionsupporting
confidence: 89%
“…A study conducted in subjects with alcoholic cirrhosis showed a higher incidence of sudden death in subjects with longer QT interval (12). Other studies showed a higher risk of sudden cardiac death in subjects with cirrhosis in treatment with drugs potentially linked to lengthening of QT interval (25e27).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Over the last 2 decades, there is accumulating evidence to suggest that the presence of cirrhosis per se is associated with significant cardiovascular abnormalities, irrespective of the cause of cirrhosis. These include resting increased cardiac output; decreased systemic vascular resistance [1]; reduced myocardial contractility or systolic incompetence, especially under conditions of stress, whether physiological [5], physical [6,7], or pharmacological [8]; increased thickness of the left ventricle [9][10][11], associated with diastolic dysfunction; and electrophysiological abnormalities [12][13][14]. This constellation of abnormalities has been termed cirrhotic cardiomyopathy [15].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has demonstrated an alteration related to ventricular repolarization, such as QT and QTc intervals, in pregnant women with preeclampsia (15). Furthermore, many studies have reported a clinical utility of QT d as a prognostic factor for mortality in several diseases (16,17).…”
Section: Introductionmentioning
confidence: 99%